2018
DOI: 10.1007/s40831-018-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Iron Recovery from Bauxite Residue Through Reductive Roasting and Wet Magnetic Separation

Abstract: The scope of this work is to develop and optimize a reductive roasting process followed by wet magnetic separation for iron recovery from bauxite residue (BR). The aim of the roasting process is the transformation of the nonmagnetic iron phases found in BR (namely hematite and goethite), to magnetic ones such as magnetite, wüstite, and metallic iron. The magnetic iron phases in the roasting residue can be fractionated in a second stage through wet magnetic separation, forming a valuable iron concentrate and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 12 publications
3
24
0
Order By: Relevance
“…Evidently, iron grains in the samples obtained without additions (Figure 16c,d) attached to the gangue phase and mainly had a size of 1-5 μm (Figure 13), so it was difficult to separate them from each other. These observations were consistent with other studies [23,30]. Although iron grains in the samples obtained with 17.1% Na2CO3 and 22.01% K2CO3 additions had a larger size, they also attached to the gangue phase, which resulted in the failure of magnetic separation (Figure 16a,b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Evidently, iron grains in the samples obtained without additions (Figure 16c,d) attached to the gangue phase and mainly had a size of 1-5 μm (Figure 13), so it was difficult to separate them from each other. These observations were consistent with other studies [23,30]. Although iron grains in the samples obtained with 17.1% Na2CO3 and 22.01% K2CO3 additions had a larger size, they also attached to the gangue phase, which resulted in the failure of magnetic separation (Figure 16a,b).…”
Section: Discussionsupporting
confidence: 92%
“…Reduction roasting is more economically viable than reduction smelting because it consumes less energy. However, the magnetic separation of iron obtained after reduction roasting of red mud at a temperature range of the solid-phase reaction has a low efficiency due to a very small size of iron grains attached to calcium aluminosilicate phases [23]. Many authors showed that addition of sodium salts promotes the iron grain growth during carbothermic reduction, for example for limonite (FeO(OH)•nH 2 O) [24], titanomagnetite (Fe 2+ (Fe 3+ ,Ti) 2 O 4 ) [25], siderite (FeCO 3 ) [26], and nickeliferous laterite ((Fe,Ni)O•OH) [27] ores.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Iron oxide as the major constituent is about 35-55% in the red mud depending on the bauxite characteristics. 20,21 Recovery of iron from red mud has been a matter of research for many years. Carbothermic reduction is mainly used to convert Fe 2 O 3 into Fe 3 O 4 and separate by magnetic separation.…”
Section: Introductionmentioning
confidence: 99%
“…The options for iron recovery investigated in the RED-MUD project include roasting and smelting processes. Roasting (at temperatures ranging from 500 °C to over 1000 °C [17,18]) is used to transform the iron in BR into magnetic forms (metallic iron, maghemite and magnetite [17]). The magnetic fraction, separated using magnetic separation, can potentially be used as a feed for direct reduction to 'sponge iron' [14], which in turn can be used as a replacement for iron scrap in the production of steel via the electric arc furnace method.…”
Section: Bulk Metals: Iron and Aluminiummentioning
confidence: 99%